CARNIVALIZATION IN DANARTO’S ASMARALOKA: A STUDY OF BAKHTINIAN DIALOGISM - Sri Wahyuningtyas; Herning Puspitarini (POETIKA, 2021)
Asmaraloka, a novel written by Danarto, is a non-realistic novel that contains many voices, ideas, discourses, and thoughts that construct the carnivalesque elements in the novel. Within the context of diversity and various phenomena in the world, the carnivalization of the story shapes the behaviors and the identities of the characters in it.Drawing on this idea, this study aims to reveal the internal and external elements that contribute to the carnivalization of Asmaraloka. The novel’s text is examined qualitatively using Bakhtinian dialogism and a sociological approach to dialogic behavior for the purpose of understanding the complete construction of meanings as the reflection of the author’s world view.The study finds that there are two categories of carnivalesque elements in Asmaraloka, namely the external and internal elements of carnival. The external carnivalization of the story creates the non-realistic world in it in relation to other texts that contribute to the diversity of ideas/ meanings in the novel. The internal carnivalization of the story generates the following structural aspects: (1) the battlefield as a means of carnival performance, (2) the occurrence of an abnormal human relationship between the characters, (3) the carnivalesque phenomena that are constructed in the story through the dialogues between peace and chaos and between obedience and denial, and (4) the effects of carnivalesque behaviors on the characters’ personality. Asmaraloka merupakan novel nonrealis karya Danarto yang berisi banyak suara, gagasan, wacana, dan pemikiran yang membentuk unsur-unsur karnival di dalamnya. Dalam konteks keberagaman dan berbagai fenomena di dunia, karnivalisasi karya sastra merupakan hal yang dapat mempengaruhi tingkah laku dan pembentukan jati diri para tokoh dalam cerita.Berkaitan dengan gagasan di atas, penelitian ini bertujuan mengungkap karnivalisasi teks Asmaraloka baik yang bersifat internal maupun yang eksternal dan pengaruhnya terhadap pembentukan karakter dari tokoh-tokoh dalam novel Asmaraloka. Penelitian ini menggunakan metode kualitatif. Analisis dilakukan berdasarkan dialogisme Bakhtin dan pendekatan sosiologis pada perilaku dialogis untuk memahami jalinan makna utuh sebagai pandangan dunia pengarang. Hasil penelitian menunjukkan adanya unsur karnival eksternal dan internal yang membangun cerita.Karnivalisasi eksternal membentuk dunia nonrealis dari cerita dan berkaitan dengan teks-teks lain yang berperan membangun keragaman makna dalam Asmaraloka. Karnivalisasi internal cerita mengungkap adanya aspek-aspek berikut ini: (1) medan pertempuran sebagai sarana pertunjukkan, (2) hubungan manusia yang tidak normal yang terjadi antar tokoh, (3) fenomena-fenomena karnivalistik yang terbangun melalui interaksi antara kedamaian dan kekacauan dan juga antara ketaatan dan pengingkaran, dan (4) unsur-unsur karnival yang merupakan dialog antara gagasan pengarang dan fenomena-fenomena sosial di masyarakat.